"Mapping suicide prevention initiatives targeting Indigenous Sámi in Nordic countries" - Jon Petter A. Stoor; Heidi A. Eriksen; Anne C. Silviken (BMC, 2021)
Abstract Background Suicide is a major public health issue among Indigenous Sámi in Nordic countries, and efforts to prevent suicide in the Sámi context are increasing. However, there is no literature on suicide prevention initiatives among Sámi. The aim of the study was to map suicide prevention initiatives targeting Sámi in Norway, Sweden, and Finland during 2005-2019. Method Initiatives were identified and described through utilizing networks among stakeholders in the field of suicide prevention among Sámi, acquiring documentation of initiatives and utilizing the authors first-hand experiences. The described initiatives were analyzed inspired by the "What is the problem represented to be?" (WPR)-approach. Results Seventeen initiatives targeting Sámi were identified during 2005-2019, including nine in Sweden, five in Norway, one in Finland and two international initiatives. Analysis with the WPR-approach yielded 40 problematizations regarding how to prevent suicide among Sámi, pertaining to shortcomings on individual (5), relational (15), community/cultural (3), societal (14) and health systems levels (3). All initiatives were adapted to the Sámi context, varying from tailor-made, culture-specific approaches to targeting Sámi with universal approaches. The most common approaches were the gatekeeper and mental health literacy training programs. The initiatives generally lacked thorough evaluation components. Conclusion We argue that the dominant rationales for suicide prevention were addressing shortcomings on individual and relational levels, and raising awareness in the general public. This threatens obscuring other, critical, approaches, such as broadening perspectives in prevention planning, improving health systems for Sámi, and promoting cultural empowerment among Sámi. Nevertheless, the study confirms considerable efforts have been invested into suicide prevention among Sámi during the last 15 years, and future initiatives might include a broader set of prevention rationales. To improve evaluation and identify the most promising practices, increased support regarding development of plans and implementation of evaluation components is needed.